Comparative efficacy of neuromodulation and structured exercise program on pain and muscle oxygenation in fibromyalgia patients: a randomized crossover study - Rubio-Zarapuz, Alejandro; Apolo-Arenas, María Dolores; Tornero-Aguilera, José Francisco; Parraca, Jose A.; Clemente-Suárez, Vicente Javier (Frontiers in Physiology, 2024)
This study investigates the comparative efficacy of neuromodulation therapy using the EXOPULSE Mollii Suit and a structured exercise program in pain modulation and muscle oxygenation in Fibromyalgia patients. A randomized, cross-sectional, longitudinal, and experimental study design was employed, involving 10 female Fibromyalgia patients. Participants were subjected to two distinct treatment modalities: neuromodulation therapy with the EXOPULSE Mollii Suit and a strength-based High-Intensity Interval Training (HIIT) exercise program, each conducted over 16 sessions. Outcome measures included pain severity, assessed using the Numeric Rating Scale (NRS), and muscle oxygenation variables measured via Near-Infrared Spectroscopy (NIRS). Both interventions demonstrated significant reductions in NRS scores and improvements in muscle oxygenation. However, the exercise program yielded more pronounced long-term basal adaptations in muscle oxygenation compared to the neuromodulation therapy. The findings underscore the potential of integrating non-pharmacological treatments, particularly structured exercise programs, in managing Fibromyalgia. While neuromodulation therapy presents a viable alternative, the exercise regimen's capacity to induce basal muscle oxygenation adaptations suggests its superiority in addressing the complex symptoms of Fibromyalgia. Furthermore, these therapeutic approaches may enhance patients'